Densidades populacionais de caupi-hortaliça consorciadas com beterraba em diferentes arranjos espaciais - Chaves, Aridênia Peixoto (Universidade Federal Rural do Semi-Árido, 2017)
Among the crops that can be successfully intercropped are cowpea-vegetable and beet. These cultures are distinguished in their architecture and exploitation of natural resources. In this sense, the objective of this work was to evaluate agronomic advantage and bio-agroeconomic return of cowpea-vegetable intercropped with beet at different population densities and spatial arrangements. The experimental design was in randomized blocks with treatments arranged in a 4 x 3 factorial scheme, with four replications. The first factor was constituted by the population densities of cowpea-vegetable (40, 60, 80 and 100% of the recommended population in the single crop - RPSC) in association with beet and the second factor constituted by three spatial arrangements (2: 2, 3: 3 and 4: 4), formed by rows of beets (B) alternated with rows of cowpea-vegetable (C). The characteristics evaluated in the cowpea-vegetable were: length of green pod, number of green pods per m2, productivity and dry mass of green pods, number of grains per pod, weight of 100 green grains, productivity and dry mass of green grains. The characteristics evaluated in the beet were: plant height, fresh mass of shoot, diameter and dry mass of roots, total, commercial and classified productivity of roots in extra, extra A, extra AA, great and scrap. The bio-agroeconomic behavior of the intercroping beet and cowpea-vegetable system was evaluated through the index of overcoming, competition rate, real income loss, intercropping advantage, land equivalente ratio, beet equivalent production index, index of productive efficiency, gross income, net income, rate of return and profitability index. The greater agronomic advantage of the intercropping cowpea-vegetable and beet was reached in the density of 95.20%. The highest bio-agroeconomic return of the intercropping of cowpeavegetable and beet was reached in the population of 40% of RPSC of cowpea-vegetable. Cowpea-vegetable was the most aggressive crop in the intercropping system with beet. There was no influence of the spatial arrangements between the component cultures on the bioagroeconomic efficiency of the intercropping of beet and cowpea-vegetable
Population densities of cowpea-vegetable intercropped with beets in different spatial arrangements
Keywords: Beta vulgaris; Vigna unguiculata; Competição intra e interespecífica; Beta vulgaris; Vigna unguiculata; Intra and interspecific competition; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA